Vascular Polyurethane Prostheses Modified with a Bioactive Coating—Physicochemical, Mechanical and Biological Properties - Aleksandra Kuźmińska (MDPI AG, 2021)
This study describes a method for the modification of polyurethane small-diameter (5 mm) vascular prostheses obtained with the phase inversion method. The modification process involves two steps: the introduction of a linker (acrylic acid) and a peptide (REDV and YIGSR). FTIR and XPS analysis confirmed the process of chemical modification. The obtained prostheses had a porosity of approx. 60%, Young’s Modulus in the range of 9–11 MPa, and a water contact angle around 40°. Endothelial (EC) and smooth muscle (SMC) cell co-culture showed that the surfaces modified with peptides increase the adhesion of ECs. At the same time, SMCs adhesion was low both on unmodified and peptide-modified surfaces. Analysis of blood-materials interaction showed high hemocompatibility of obtained materials. The whole blood clotting time assay showed differences in the amount of free hemoglobin present in blood contacted with different materials. It can be concluded that the peptide coating increased the hemocompatibility of the surface by increasing ECs adhesion and, at the same time, decreasing platelet adhesion. When comparing both types of peptide coatings, more promising results were obtained for the surfaces coated with the YISGR than REDV-coated prostheses.